Factors that Play a Role in Community Participation in Creating Healthy Alleys in Makassar City - Adhe Yuniar Batari Lipu (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2023)
This research aims to reveal the factors that play a role in community participation in creating Healthy Hallways. This research is qualitative research using a Rapid Assessment Procedures design. The informants for this research were determined using purposive sampling. The data collection technique used in-depth interviews with seven community members: 1 RT head, 1 RW head, 1 Community Health Center staff, two health cadres, and one village head. This research was analyzed using the